Binary Option: Legality in the Perspective of National and Islamic Law as a Manifestation of Continuous Legal Reform (Semarang State University Undergraduate Law and Society Review, 2023)
Law is used as a guide and protector for every human being who lives in society, there are several kinds of applicable law in Indonesia, namely Indonesian national law and Islamic law. Amid the development of increasingly sophisticated digital technology, digital investment methods in the form of Binary Options have emerged which cause problems in people's lives. Then this research was conducted to determine the position of Binary Options in the perspective of national law and Islamic law so that the public knows and understands the legal basis for investing in the form of Binary Options. The writing of this journal uses normative juridical research methods. The results of the analytical study were obtained that in national law Binary Options as an illegal act which is part of an unlawful act, one of which is the result of not getting permission from the OJK (Financial Services Authority) so that it can be sentenced to criminal sanctions, while in the perspective of the Islamic law that Binary Options Judging from the way the game is played, it can be said that gambling is more precisely modern gambling, where gambling itself in Islam is strictly prohibited based on the verses of the Qur'an